1972
DOI: 10.1172/jci106889
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum and Urinary Calcium during Treatment with Hydrochlorothiazide: Studies on Mechanisms

Abstract: A B S T R A C T Studies were undertaken in man to evaluate the roles of volume depletion and of the parathyroid glands in mediating the changes in serum and urinary calcium which follow the administration of hydrochlorothiazide, 100 mg twice daily, for 4 days. 42 studies were carried out in 16 normal subjects, 9 patients with hyperparathyroidism, and 7 vitamin D-treated subjects with hypoparathyroidism. In six studies in normal subjects, daily sodium losses during thiazide administration were quantitatively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
83
3
3

Year Published

1973
1973
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(95 citation statements)
references
References 27 publications
6
83
3
3
Order By: Relevance
“…Creatinine clearance, Ca filtered load, and urine Na excretion were not altered by chronic TZ treatment. A modest drop in intravascular volume has been shown to occur after initiation of TZ in other studies (7,34), after which subjects come into balance at this new modestly decreased weight, and Na excretion returns to baseline; presumably volume depletion occurred in our subjects as well ( Table 1).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Creatinine clearance, Ca filtered load, and urine Na excretion were not altered by chronic TZ treatment. A modest drop in intravascular volume has been shown to occur after initiation of TZ in other studies (7,34), after which subjects come into balance at this new modestly decreased weight, and Na excretion returns to baseline; presumably volume depletion occurred in our subjects as well ( Table 1).…”
Section: Discussionsupporting
confidence: 66%
“…The mechanism of chronic TZ hypocalciuria is unclear. In short-term studies, administration of TZ causes modest Na depletion, which is associated with a fall in urine Ca excretion; the hypocalciuria can be prevented by administration of sodium chloride (6,7,30,32). However, these studies have rarely included subjects with IH and usually were limited to a week or less in duration.…”
mentioning
confidence: 99%
“…Parfitt (18) and Higgins et al (12) reported that thiazides were effective in decreasing the amount of calcium in the urine of vitamin-D-treated patients. Yendt and Cohanim (24), Parfitt (19), and Brickman et al (3), who studied patients with hypoparathyroidism treated by vitamin-D, found that thiazide had no influence on the excretion of calcium; on the other hand, normal controls receiving vitamin-D studied by the last group (3) experienced reduction in calcium excretion rates under treatment. Harrison and Harrison (11) pressed for further controlled studies of thiazide therapy for vitamin-D-induced hypercalciuria before conclusions should be drawn about their applicability in man.…”
Section: Methodsmentioning
confidence: 99%
“…Previous attempts to evaluate the effect of thiazides on vitamin-D-induced hypercalciuria have RESULTS produced the conflicting claims that urine calcium excretion is reduced in some patients (12,18) but that it is not reduced in All rats consumed 16 2 g of the Purina chow and lost 2.1 * others (3,19,24). It has, therefore, been recommended that further 1.2% of their weight during the 12-day study, with no difference studies are needed ( I 1).…”
mentioning
confidence: 99%
“…Thiazide diuretic agents and analogous molecules such as chlorthalidone (Thz) reduce urine calcium excretion in normal people (22,23), patients with idiopathic hypercalciuria (24,25), hypoparathyroid people (26,27), and rats (28,29). Thiazide diuretics are commonly used to treat CaOx stone disease (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%